Pengaruh Beban Kerja terhadap Kedisiplinan Petugas Aviation Security di Bandar Udara Internasional Supadio Pontianak - Krismanto Krismanto; Amelia Puspa Tamara (Pusat Riset dan Inovasi Nasional, 2023)
Airports have a very important role in the smooth process of passengers who will make flights, the workforce at the airport in carrying out their duties needs to be done quickly and precisely as well as the duties and responsibilities of Aviation Security (AVSEC). This includes the duties of AVSEC in ensuring flight security and safety, As an International Airport that has a large number of passengers, Supadio Pontianak International Airport needs to maintain passenger comfort in terms of security and service. This study aims to determine the effect of workload on the discipline of Aviation Security officers at Supadio Pontianak International Airport and to determine how much influence workload has on the discipline of Aviation Security officers at Supadio Pontianak International Airport. This research was conducted on Aviation Security officers at Supadio Pontianak International Airport, while the research time was for 30 days from October 1 - October 31, this study used a quantitative approach method, with Aviation Security officers as Research Subjects, the population in this study amounted to 81 and used a sample of 81 respondents, the data used in this study were primary data in the form of questionnaires through google form, before the research was carried out, the instrument was first tested with a validity test and reliability test involving 81 avsec personnel at supadio pontianak international airport. The results of this study indicate a positive influence on workload (X) on discipline (Y) on Avsec personnel at the international airport supadio pontianak, Based on the results of the study, it can be seen that the R square value is 0, 180 or equal to 18%, meaning that the workload variable (X) affects the discipline variable (Y) by 18%, while the remaining 100% - 18% = 82% is influenced by other variables outside the regression equation or variables that are not studied. Keywords: The Effect of Workload on the Discipline of Aviation Security Officers.